Optimalisasi Pembangkitan Daya Panel Surya 200 WP Menggunakan Solar Tracker System Dual Axis - Erwan Eko Prasetiyo; Gaguk Marausna; Dimas Wahyu Nugroho (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2022)
Electrical energy is the main commodity used by almost all sectors of the economy. Therefore, the Indonesian people’s demand for electrical energy is getting higher nowadays. The growing electricity demand is inversely proportional to the dwindling availability of fossil energy in the world. Energy sources from the sun can be utilized as alternative energy, both its radiation and thermal, to meet daily electrical energy demand. This study aims to optimize the electrical energy production from solar panels with a capacity of 200 WP by designing and implementing a dual axis solar tracker system on solar panels (photovoltaic). This research employed a mixed methods approach, i.e., designing a solar tracker system experimentally by measuring the voltage and current values on solar panels, then calculating the electrical power generated by solar panels using solar tracker system control. After that, the calculation of electrical power generated by solar panels and electrical power used (load) by the solar tracker system to control the solar panel movement following the sunlight emission was conducted. Solar tracker controlled with a single axis produced an average voltage of 19.72 V, current of 1.34 A, and electrical power of 26.82 W, while solar tracker controlled with a dual axis generated an average voltage of 18.93 V, current of 1.9 A, and electrical power of 35.76 W. The test results showed that the total electrical power generated by solar panels with a single axis solar tracker system control system was 455.93 W and a dual axis solar tracker system was 607.94 W. Data of testing results showed that the dual axis solar tracker system was able to optimize electrical energy production yielded by solar panels with a capacity of 200 WP.